Angular reconstruction of high energy air showers using the radio signal spectrum. (29th June 2020) - Nonis, S; Leisos, A; Tsirigotis, A; Bourlis, G; Papageorgiou, K; Gkialas, I; Manthos, I; Tzamarias, Spyros
Abstract: The Hellenic Open University extensive air shower array (also known as Astroneu array) is a small scale hybrid detection system operating in an area with high levels of electromagnetic noise from anthropogenic activity. In the present study we report the latest results of the data analysis concerning the estimation of the shower direction using the spectrum of the RF system. In a recent layout of the array, 4 RF antennas were operating receiving a common trigger from an autonomous detection station of 3 particle detectors. The directions estimated with the RF system are in very good agreement with the corresponding estimations using the particle detectors demonstrating that a single antenna has the potential for reconstructing the shower axis angular direction.